O korespondencji dyrektyw redagowania i interpretowania tekstu prawnego: [Correspondence between instructions on formulating and interpreting of a legal text] (Studia Prawnicze / The Legal Studies, 1985)
Subject interested in legal texts insist on their careful and most accurate and, at the same time, clear formulation. In order to meet these requirements, there should be correspondence between instructions on their formulating and interpreting. The task of the present article is to answer the question: whether the correspondence between instructions on formulating and interpreting of legal texts is possible and desirable. According to the authors, it is possible to achieve such correspondence through the adjustment of already existing instructions on formulation and interpretation of such texts. The authors attempted to distinguish certain types of instructions for which such correspondence is necessary or useful, illustrating them by examples of instructions based either on regularity of formulation or interpretation of the text or intuition. The set of those instructions which should correspond with each other is a starting point for a full catalogue of ‘instructions in question.In the final part of the work the authors consider various variants of the reform of language of legal texts. They speak in favour of a moderate reform, i.e. reform which takes into account the existing and verified instructions and disregards instructions which do not serve the correspondence and replace them by new ones. Such a reform should be initiated by the legislator. However, it has to meet various requirements which were discussed in the article.